Volume 4: Fluid-Structure Interaction 2016
DOI: 10.1115/pvp2016-63334
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis and the Role of Normal Form Symmetries on the Harmonic Forced Inline Oscillation of the Cylinder Wake

Abstract: Vortex shedding over a cylinder is strongly affected by the cylinder oscillation. The dynamics of the cylinder wake subjected to harmonic forced excitation in the inline direction at Re = 200 is investigated in this work. Two dominant modes of the transverse velocity field are considered to model and predict the nonlinear interaction of 2D vortex shedding. The normal form symmetries have the main role in the pattern formation. The interaction of two steady modes in the presence of O(2) × S1 symmetry is describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the previous studies [24]- [26], it was shown that, using POD analysis, 2D wake has two fastest growing modes containing almost 90% of the total fluctuating energy in different flow regimes. These modes were therefore used to model the flow dynamics.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
See 1 more Smart Citation
“…In the previous studies [24]- [26], it was shown that, using POD analysis, 2D wake has two fastest growing modes containing almost 90% of the total fluctuating energy in different flow regimes. These modes were therefore used to model the flow dynamics.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…The pulsed plasma actuation is simulated in ANSYS-CFX with addition of a source term to the momentum equation; The mesh convergence test was performed in [24]- [26]. The 0.06…”
Section: Numerical Set Upmentioning
confidence: 99%